Online Peer-to-Peer Communities in the Daily Lives of People With Chronic Illness: A Qualitative Systematic Review. (January 2017) - Kingod, Natasja; Cleal, Bryan; Wahlberg, Ayo; Husted, Gitte R.
This qualitative systematic review investigated how individuals with chronic illness experience online peer-to-peer support and how their experiences influence daily life with illness. Selected studies were appraised by quality criteria focused upon research questions and study design, participant selection, methods of data collection, and methods of analysis. Four themes were identified: (a) illness-associated identity work, (b) social support and connectivity, (c) experiential knowledge sharing, and (d) collective voice and mobilization. Findings indicate that online peer-to-peer communities provide a supportive space for daily self-care related to chronic illness. Online communities provided a valued space to strengthen social ties and exchange knowledge that supported offline ties and patient–doctor relationships. Individuals used online communities to exchange experiential knowledge about everyday life with illness. This type of knowledge was perceived as extending far beyond medical care. Online communities were also used to mobilize and raise collective awareness about illness-specific concerns.